Differential Protein Expression in Human Dental Pulp: Comparison of Healthy, Inflamed, and Traumatic Pulp - Yue, Wonyoung (J Clin Med, 2019)
Trauma or injury to the dental pulp causes inflammation. This study compared the proteome of healthy pulp with inflamed pulp and traumatic pulp to identify the differentially expressed proteins in the diseased state. Five participants were grouped based on the pulpal status of the teeth: healthy, inflamed, or traumatic pulp. Pulp was extirpated and stored immediately in liquid nitrogen. Pulp tissues were subjected to 2-dimensional gel electrophoresis, and spot selection was performed. The selected spots were analyzed using liquid chromatography-tandem mass spectrometry and identified by correlating mass spectra to the proteomic databases. Fifteen spots showed increased expression in the inflamed and traumatic pulp. Annexin V, type II keratin, and hemoglobin levels were increased two-fold in the inflamed and traumatic pulp group and annexin V, mutant beta-actin, and hemoglobin were increased by ten-fold in the inflamed or traumatic pulp group, compared to levels in the healthy pulp group. Annexin V constituted two out of fifteen protein spots, and seemed to play a critical role in inhibiting inflammation and promoting the immune reaction. Further studies on this protein concerning its role in pulp repair are necessary to elucidate the underlying mechanisms.